MLH1 focus mapping in the guinea fowl (Numida meleagris) give insights into the crossover landscapes in birds - del Priore, Lucía (2020)
Crossover rates and localization are not homogeneous throughout the genomes. Along the chromosomes of almost all species, domains with high crossover rates alternate with domains where crossover rates are significantly lower than the genome-wide average. The distribution of crossovers along chromosomes constitutes the recombination landscape of a given species and can be analyzed at broadscale using immunostaining of the MLH1 protein, a component of mature recombination nodules found on synaptonemal complexes during pachytene. We scored the MLH1 foci in oocytes of the chicken and the guinea fowl and compared their frequencies in the largest bivalents. The average autosomal number of foci is 62 in the chicken and 44 in the guinea fowl. The lower number in the guinea fowl responds to the occurrence of fewer crossovers in the six largest bivalents, where most MLH1 foci occur within one-fifth of the chromosome length with high polarization towards opposite ends. The skewed distribution of foci in the guinea fowl contrast with the more uniform distribution of numerous foci in the chicken, especially in the four largest bivalents. The crossover distribution observed in the guinea fowl is unusual among Galloanserae and also differs from other, more distantly related birds. We discussed the current evidence showing that the shift towards crossover localization, as observed in the guinea fowl, was not a unique event but also occurred at different moments of bird evolution. A comparative analysis of genome-wide average recombination rates in birds shows variations within narrower limits compared to mammals and the absence of a phylogenetic trend.